Evaluation of Contemporary Trends in Femoral Neck Fracture Management Reveals Discrepancies in Treatment. (September 2016) - Bishop, Julius; Yang, Arthur; Githens, Michael; Sox, Alex H. S.
Background: Recent evidence supports total hip arthroplasty (THA) as compared to hemiarthroplasty (HA) for the management of displaced femoral neck fractures in a significant subset of elderly patients. The purpose of this study was to examine trends in femoral neck fracture management over the last 12 years. Methods: Using the National Inpatient Sample database, we identified patients treated for femoral neck fractures between 1998 and 2010 with THA, HA, or internal fixation (IF). We examined treatment trends and demographic variables including patient age, gender, socioeconomic status, and payer and hospital characteristics. Results: We identified 362 127 femoral neck fracture patients treated between 1998 and 2010. Overall, there were statistically significant increases in rates of THA and HA, whereas rates of IF decreased. Total hip arthroplasty varied based on patient age, with significant increases occurring in age-groups 0 to 49 years, 50 to 59 years, 60 to 69 years, and 70 to 79 years. Utilization of THA varied significantly based on socioeconomic status and race. Patient sex, urban versus rural hospital location, and teaching versus nonteaching hospital status were not related to rates of THA. Conclusion: Rates of THA for femoral neck fractures increased between 1998 and 2010 in patients younger than 80 years, suggesting that surgeons are responding to clinical evidence supporting THA for the treatment of elderly femoral neck fractures. This is the first study to demonstrate this change and expose disparities in practice patterns over time in response to this evidence in the United States. Further research is indicated to explore the effect of socioeconomic status and race on femoral neck fracture management.